2020
DOI: 10.1186/s12877-020-1472-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a polyphenol-rich dietary pattern on intestinal permeability and gut and blood microbiomics in older subjects: study protocol of the MaPLE randomised controlled trial

Abstract: Background: During aging, alterations of the intestinal microbial ecosystem can occur contributing to immunosenescence, inflamm-aging and impairment of intestinal barrier function (increased intestinal permeability; IP). In the context of a diet-microbiota-IP axis in older subjects, food bioactives such as polyphenols may play a beneficial modulatory role. Methods: MaPLE is a project centered on a randomized, controlled cross-over dietary intervention trial [polyphenol-rich diet (PR-diet) versus control diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 51 publications
0
72
0
Order By: Relevance
“…ticipants were recruited from residents at Civitas Vitae, a dation including both nursing homes and independent y) according to specific inclusion and exclusion criteria. to be aged 60 years and to have increased intestinal level as previously reported [16]. e study were self-sufficient and were in good cognitive ersità degli Studi di Milano approved the study protocol _All-7).…”
Section: Study Design and Populationmentioning
confidence: 88%
See 4 more Smart Citations
“…ticipants were recruited from residents at Civitas Vitae, a dation including both nursing homes and independent y) according to specific inclusion and exclusion criteria. to be aged 60 years and to have increased intestinal level as previously reported [16]. e study were self-sufficient and were in good cognitive ersità degli Studi di Milano approved the study protocol _All-7).…”
Section: Study Design and Populationmentioning
confidence: 88%
“…The study design of the MaPLE randomized controlled trial (RCT) has been previously reported [16]. Briefly, the central hypothesis that this study sought to address was that a polyphenol-enriched dietary pattern would reduce IP and systemic inflammation and cause beneficial changes in various biomarkers of cardiometabolic health, and that this would be associated with changes in the gut microbiota in these older subjects.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 3 more Smart Citations